From 'T' to 'π' (pi)‐shaped people: Better Urban Practice through Dual Depth in Architecture and Planning Education. (31st March 2020) - Burry, Jane; White, Marcus
Abstract: What sorts of educational methodologies and pedagogic theories are we to teach young, student architects and other environmental design professionals? How can we prepare students just starting to develop appropriate skills in the third decade of the 21st century? Jane Burry and Marcus White, respectively Dean of the School of Design and Professor of Urban Design at Swinburne University in Melbourne, describe some of the attempts to find ways forward and appropriate organisational structures.